Inflation, output and perfectly enforceable price controls in orthodox and heterodox stabilization programmes - Mario Reyna-Cerecero; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper deals with the success of price controls in stabilizing high inflation rates and their effects on the real economy under an imperfect competition setting derived by optimal maximization. Our model builds on Helpman's work of price controls and imperfect competition, and incorporates inflation inertia through adaptive expectations. The model predicts that under these circumstances price controls can be an effective method of curving inflation when they accompany an orthodox monetary restriction programme; incomes policies alone cannot curve inflation substantially. Efforts where monetary growth is decreased gradually and price controls are implemented to achieve zero inflation result in the boom-recession cycle observed in many real life programmes. When monetary growth is curved immediately and price controls are implemented to achieve zero inflation, there follows a recession and not a boom. Orthodox money-based stabilization programmes implemented on their own need more time to control inflation and always produce a recession.
Keywords: E64; E31; 330; stabilization programmes; inflation; price controls; Inflationsbekämpfung; Staatliche Preispolitik